Pelaksanaan Tugas Pengawasan dan Pemantauan Lingkungan pada Dinas Lingkungan Hidup Kabupaten Sukoharjo - Sinung Bagas Pramuaji; I Gusti Ayu Ketut Rachmi Handayani (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
The aims of this research is to find out the implementation of the duties and authority of the Environmental Department of Sukoharjo Regency in conducting environmental supervision and monitoring, especially the quality of the Samin River water and the obstacles it experiences. This research uses empirical legal research method or non-doctrinal research. The type of data used is primary data that was obtained from field data which is the object of research, namely the Sukoharjo Environmental Department, and uses primary legal materials, namely statutory regulations and uses secondary legal materials in the form of relevant books and articles. Based on the results of the research, the authors obtained the answers of the problem of the Environmental Department of Sukoharjo Regency in conducting environmental supervision and monitoring by conducting field observations and sampling of river water, laboratory testing of water samples, and supervising and coaching alcohol craftsmen in Ngombakan Village who throw away their garbage into the river. Then, the obstacles experienced by the Environmental Department of Sukoharjo are the lack of budget for monitoring funds and the lack of public awareness to protect the environment by not throwing away their garbage directly into the river.